Presentation of Vol. 5 Num. 1 (2024): February - May 2024 - Zegarra López, Fernando Elías (2024)
The complexity of National Security and its intimate relationship with National Development reveals the importance of promoting the laudable purpose of achieving higher levels of general well-being of the national population. The articles in this edition confirm the importance and validity of the comprehensive and multidimensional approaches that require a holistic and coordinated treatment of the National Defense System, as well as the adequate use of the instruments of national power established in the regulations of Legislative Decree 1129 , which is why from this academic faculty we reaffirm our commitment to present ideas, analyzes and articles that present diagnoses of our reality, as well as proposals to benefit the security and well-being of Peru. There is no other interest.